2019
DOI: 10.1002/maco.201810247
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behavior of austenitic steel Sanicro25 and TP347HFG in supercritical water

Abstract: Oxidation tests of austenitic steel Sanicro25 and TP347HFG were implemented at 600–700 °C in supercritical water under 25 MPa without dissolved oxygen. With an increase in temperature, the weight change of TP347HFG steel increases significantly while the weight change of Sanicro25 increases relatively slow. A double layer oxide scale formed on TP347HFG and Sanicro25 steel, which was composed of Fe‐rich oxide layer and a Cr‐rich inner oxide layer. Small amount of Cr2O3 was observed for TP347HFG but a continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…Indeed, within the shown grain (Figure 11), metallic un-oxidised zones can still be observed inside the grain. Lath preferential oxidation was also observed by Bischoff and coworkers on ferritic steels [31] and similar microstructures were observed by Li [8] Yang [19] and Tepylo [26] and coworkers on 304 H stainless steel and by Zhu et al on TP347HFG stainless steel [32] after steam oxidation. In agreement with Chen and coworkers' findings [11], the formation of Cr-rich layers in this inner oxide leads to Cr depletion and indeed, on the areas surrounding the nodules, Cr depletion can be observed on the element map showed in Figure 9.…”
Section: Microstructure Of the Oxide Scales Developed Under Atmospheric Steamsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, within the shown grain (Figure 11), metallic un-oxidised zones can still be observed inside the grain. Lath preferential oxidation was also observed by Bischoff and coworkers on ferritic steels [31] and similar microstructures were observed by Li [8] Yang [19] and Tepylo [26] and coworkers on 304 H stainless steel and by Zhu et al on TP347HFG stainless steel [32] after steam oxidation. In agreement with Chen and coworkers' findings [11], the formation of Cr-rich layers in this inner oxide leads to Cr depletion and indeed, on the areas surrounding the nodules, Cr depletion can be observed on the element map showed in Figure 9.…”
Section: Microstructure Of the Oxide Scales Developed Under Atmospheric Steamsupporting
confidence: 81%
“…In fact, the original substrate grains appear to be surrounded by a Cr-and Mn-rich oxide, and inside the grains, preferential lath boundary oxidation takes place, as exhibited in the EDS element map shown in Figure 11. This confirms that oxygen inwards diffusion Yang [19] and Tepylo [26] and coworkers on 304 H stainless steel and by Zhu et al on TP347HFG stainless steel [32] after steam oxidation. In agreement with Chen and coworkers' findings [11], the formation of Cr-rich layers in this inner oxide leads to Cr depletion and indeed, on the areas surrounding the nodules, Cr depletion can be observed on the element map showed in Figure 9.…”
Section: Microstructure Of the Oxide Scales Developed Under Atmospheric Steamsupporting
confidence: 80%
“…Cr­(OH) 3 is formed on the alloy surface and then is converted into Cr 2 O 3 via the following reactions (see reactions –). , Therefore, Cr oxides eventually exist in the form of Cr 2 O 3 . The critical Cr content in an alloy is the minimum content to form a continuous Cr 2 O 3 layer to hinder internal oxidation. The critical Cr content for the Fe–Cr alloy is expressed as follows: ,, where N Cr O is the criterion content of Cr, N δ O is the oxygen solubility in the alloy, D O is the oxygen diffusivity in the alloy, V m is the molar volume of the alloy, D̃ Fe–Cr is the interdiffusion coefficient of the alloy, V CrO 1.5 is the molar volume of Cr oxides, and the value of g * is assumed to be 0.3.…”
Section: Reactions Of Typical Elementsmentioning
confidence: 99%
“…The critical Cr content in an alloy is the minimum content to form a continuous Cr 2 O 3 layer to hinder internal oxidation. The critical Cr content for the Fe−Cr alloy is expressed as follows: 40,45,46 i k j j j j j j y…”
Section: Reactions Of Typical Elementsmentioning
confidence: 99%
“…Studies have shown that elements such as chromium, silicon, and aluminum are important elements to improve the oxidation resistance of heat-resistant materials. [3][4][5][6][7][8] Therefore, ferritic steel containing chromium is selected for the steam turbine system of conventional power plant boilers around the world. [9,10] The heatresistant materials of the steam turbine system of conventional power plant boilers have good resistance to steam oxidation under high-temperature conditions because dense and stable oxide films are formed on the steam sidewall surface.…”
Section: Introductionmentioning
confidence: 99%